Efficiency of Domestic Wastewater Utilization from Wastewater Treatment Plants for Irrigation at Bauxite Ore Mining Hauling Areas: Efisiensi Pemanfaatan Air Limbah IPAL Domestik Untuk Penyiraman Lahan Hauling Tambang Biji Bauksit - Abdul Rahman Hamidi; Tuhu Agung Rachmanto; Akmal Dzikri Maulana (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
The bauxite ore mining industry produces domestic wastewater from various supporting activities such as office facilities, employee dormitories, laboratories, contractor areas, and jetties. This wastewater has pollutant characteristics that exceed quality standards, requiring treatment through a Wastewater Treatment Plant (WWTP) before being reused. This study aims to analyze the characteristics of domestic wastewater, the WWTP treatment unit process, and the feasibility of its use for irrigation of the hauling area (a special route for material transportation). The method used is descriptive-quantitative with secondary data including clean water needs, wastewater generation, WWTP processes, laboratory test results from KAN-accredited WWTP outlets, irrigation water needs, and irrigation scenarios. The wastewater quality assessment refers to domestic wastewater quality standards as directed by the Ministry of Environment and Forestry (KLHK) in 2022, as well as Class 4 River Water Quality Standards based on Government Regulation No. 22 of 2021, which are used as a reference for wastewater utilization for irrigation. The hauling area used for irrigation covers an area of ​​7,500 m² with dimensions of 500 meters long and 15 meters wide. The study results show that domestic wastewater treatment in the bauxite ore mining industry is effective in reducing pollutant parameters and is safe for use as irrigation water for hauling areas. This wastewater utilization also contributes to water efficiency and supports sustainability principles in the mining environment.